THE DEVELOPMENT AND CREATION OF ENCYCLOPEDIC, ETYMOLOGICAL, SPELLING AND DESCRIPTIVE DICTIONARIE ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the creation and significance of four key types ofdictionaries: encyclopedic, etymological, spelling, and explanatory. It traces theirhistorical origins, development processes, and the roles they play in language and society. Encyclopedic dictionaries combine linguistic information with detailed knowledge onvarious topics, serving as repositories of cultural and scientific data. Etymologicaldictionaries reveal the historical evolution of words, while